Intraductal papillary mucinous neoplasm of the pancreas rapidly xenografts in chicken eggs and predicts aggressiveness. Issue 7 (29th November 2017) - Zhao, Zhefu; Bauer, Nathalie; Aleksandrowicz, Ewa; Yin, Libo; Gladkich, Jury; Gross, Wolfgang; Kaiser, Jörg; Hackert, Thilo; Strobel, Oliver; Herr, Ingrid
Abstract : Intraductal papillary mucinous neoplasm (IPMN) of the pancreas has a high risk of progressing to invasive pancreatic ductal adenocarcinoma (PDA), but experimental models for IPMN are largely missing. New experimental systems for the molecular characterization of IPMN and for personalized prognosis and treatment options for IPMN are urgently needed. We analyzed the potential use of fertilized chicken eggs for the culture of freshly resected IPMN tissue. We transplanted 49 freshly resected IPMN tissues into eggs and compared the growth characteristics to IPMN tissues transplanted into mice; this was followed by an analysis of histology, morphology, and marker expression. Of the IPMN tissues transplanted into eggs, 63% formed tumor xenografts within 4 days, while none of the 12 IPMN tissues transplanted into immunodeficient mice engrafted. In the eggs, the grafting efficiency of high‐grade ( n  = 14) and intermediate‐grade ( n  = 17) dysplasia was 77% and was significantly higher than the 39% grafting efficiency of low‐grade dysplasia ( n  = 18). According to mucinous expression, 46 IPMN tissues were classified into gastric ( n  = 6), intestinal ( n  = 3), oncocytic ( n  = 23), and pancreatobiliary ( n  = 14) subtypes. The grafting efficiency was highest for the pancreatobiliary subtype (86%), followed by the oncocytic (70%), gastric (33%) and intestinal (33%) subtypes. The morphology and expression patterns of mucins, progression markers and pancreatic ductal markers were comparable between the primary IPMN tissues and their xenograft copies. The individual tumor environment was largely maintained during subtransplantation, as evaluated upon passage 6. This new IPMN model may facilitate experimental studies and treatment decisions for the optimal personalized management of IPMN. Abstract : What's new? Intraductal papillary mucinous neoplasm (IPMN) is a dysplasia of the pancreas that often becomes invasive but studies of the noninvasive state are challenged by the lack of faithful model systems. Here the authors describe the successful establishment of three‐dimensional IPMN xenografts from freshly resected patient tissue in chicken eggs. The egg xenografts reflected the malignancy and morphology of the primary tumor and may thus facilitate experimental studies, treatment decisions and optimal personalized management of IPMN.